The Advertising Strategies as a Determinant for Consumer Brand Preference in Osun State, Nigeria (an INSIGHT of U.A.C FOODS PLC) - Haorayau Bolaji Babalola Babalola; Saheed Ademola Lateef Lateef; Dauda Ayodele Morakinyo (STIM LASHARAN JAYA MAKASSAR, 2021)
Several companies spend enormous amounts on advertising and still claim indifference in sales volume. This seems to be based on a completely understandable reaction to the initiative. The problem might emanate from media channel or advertising strategy itself. The study therefore, investigated effect of advertising strategies on consumer brand preference with particular reference to UAC food plc Osogbo, Osun state. It examined the choice of advertising media on consumers’ brand preference and also determined the relationship between publicity through celebrity endorsement and consumer brand preference of UAC foods plc. 140 questionnaires were administered to the target respondents using simple random sampling and correlation and multiple regression techniques were used to analyse the collected data via SPSS version 25. Result from the study shows that advertising has a significant effect on consumers’ brand preference. Publicity through celebrity endorsement also has strong relationship with consumers’ brand preference. The choice of advertising media has a significant influence on consumers’ brand preference. The study therefore recommended that advertising should be seen as an investment in the future of products and not to be evaluated by its immediate returns.